Biotechnological Tool for Metal(loid)s as Cd, Cu, Ni, and P Management with Multiple Approaches: Bioremediation, Recovery of Raw Materials, and Food Safety - Adalgisa Scotti; Ana Rosa Castaño Gañan; Vanesa Analía Silvani; Andrea Juarez; Gabriela Coria; Sofía Utge Perri; Roxana Paola Colombo; Inmaculada García-Romera; María Luisa Izaguirre-Mayoral; Alicia Godeas; Stefano Ubaldini (Metals)
Contaminated soils are a challenge for implementing biotechnology in bioremediation, the recovery of Critical and Strategic Raw Materials (CRMs and SRMs), and food security. European Union (EU) Governments have established strict limits on As, Pb, Cd, and Hg in foods (Document 32023R0915) and requested the recovery of 34 CRMs within a circular economy (CE) (5th CRMs list). This study proposed a biotechnological tool for the decontamination of soil with heavy metal(loid)s by arbuscular mycorrhizal (AM)-assisted phytoextraction and the subsequent recovery of CRMs or by phytostabilization to prevent their entry into the food chain. It consisted of placing Baccharis salicifolia plants, inoculated or non-inoculated with AM fungi, into bioreactors (BRs) containing mining soil with Cd, Ni, and Cu, according to the Argentinian Patent (AR090183B1). The bioextractive potential (BP) was also estimated at the highest Technological Readiness Level (TRL) using a vegetable depuration module (VDM, TRL 6). Inoculated plants showed significantly higher aerial bioaccumulation coefficients (Cd: 68.62; P: 2.99; Ni: 2.51; Cu: 0.18) in BRs, and the BP values reached 1.16 g, 9.75 g, 2.40 g, and 213.1 g for Ni, Cd, Cu, and P, respectively. Finally, these CRMs and SRMs could be recovered from biomass through hydrometallurgy within a CE framework.